IMTA (INTEGRATED MULTI-TROPHIC AQUACULTURE) SYSTEM APPLICATION IN WINDU SHRIMP CULTIVATION PRODUCTIVITY (LITERATURE REVIEW) - Andriani, Yuli; Hafel, Aulia Putri Kapsari; Maharani, Annisa Nur; Taufanputri, Melati; Yustiati, Ayi (Universitas Mataram, 2025)
The IMTA cultivation system is a cultivation system that combines several commodities with different trophic levels. In an effort to increase the productivity and sustainability of shrimp cultivation, the Pond-Water Integration (IMTA) system has emerged as a solution in the field of cultivation. Tiger shrimp cultivation using the IMTA system is a combination of two or three cultivation commodities, where nutritional/feed waste from higher level animals is consumed by lower level thropic animals. This research aims to determine the influence of the IMTA system on the growth of tiger prawns. The method used in this research is exploratory descriptive from various literature and research results that have been published, either from books, national journals or international journals. Based on a comparison of the results of previous research, it can be concluded that the IMTA system has a significant effect on the growth of tiger prawns, there are real differences in growth such as weight gain, relative growth rate, and survival rate of tiger prawns (P. monodon).